The Effect of Competence, Motivation, and Organizational Commitment On Performance Of Nursing - Saryadi Saryadi; Liss Dyah Dewi Arini (LPPM Universitas Duta Bangsa Surakarta, 2022)
This study examines the effect of Competence, Motivation, and Organizational Commitment On the Performance Of Nursing. A total of 60 respondents were obtained in this research with a census. Analyzed data using the path analyzed with quality of data, t-test, F-test, coefficient determination, and classic assumption. This study has no problem with classic assumptions. The result of this study shows that competence, motivation, and organizational commitment have a significant positive effect on performance partially and simultaneously. The contribution of determination coefficient (R-square) = 0,681, means that the Performance of Nursing is explained by competence, motivation, and organizational commitment of 68,1%, and the remaining 31,9 is explained by other variables outside the research model, for example, communication, discipline, and others. This study indicates that variable organizational commitment is the dominant effect on the performance of nursing.